Efficacy of Lean Metrics in Evaluating the Performance of Manufacturing Systems - Khadem, Mohammed; Ali, Sk Ahad; Seifoddini, Hamid (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
The efficacy measure is an important indicator in lean performance measure. The research is to develop a quantitative analysis framework and a simulation methodology to evaluate the efficacy of lean metrics in the production systems. A procedure for quantitative analysis of lean metrics is developed and the evaluation of the lean effectiveness in predicting the performance is presented. Lean metrics are embedded into simulation model so that the simulator is able to provide automatically lean metrics for the systems without any extra effort. The embedded lean simulation is used to investigate the significance of various improvement opportunities. This efficacy of these metrics for the performance measurement is a leading indicator for a manufacturing system. A validation is done to show the effectiveness of the proposed systems.